The First Cycle of Developing Teaching Materials for Fractions in Grade Five Using Realistic Mathematics Education - Julie, Hongki; Suwarsono, St.; Juniati, Dwi (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2013)
There are three questions that will be answered in this study, namely (1) what are the contexts that can be used to introduce the meaning of multiplication of two fractions and to find the result of multiplying two fractions, (2) how to use these contexts to help students construct the understanding of the meaning of multiplication of two fractions and find the result of multiplying two fractions, and (3) what is the impact of the teaching-learning process that has been designed by researchers on the process of students' knowledge construction. Learning approach which was used in developing teaching materials about fractions is realistic mathematics approach. Lesson plan was created for fifth grade elementary school students. The type of research used is developmental research. According to Gravemeijer and Cobb (in Akker, Gravemeijer, McKeney, and Nieveen, 2006) there are three phases in development research, namely (1) preparation of the trial design, (2) the trial design, and (3) retrospective analysis. This paper presents the results of the first cycle of three cycles that have been planned.